2004
DOI: 10.1021/jo035769j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Isomer-Pure Synthesis of a Benzo[b]thiophene Analogue of Pentacene,

Abstract: Isomer-pure thieno[3,2-f:4,5-f ']bis[1]benzothiophene (2, n = 2) has been synthesized in an efficient four step approach without column chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…[13,14] The gas-phase photoelectron spectra of TBBT and BDT were collected by using the instrument and experimental procedures reported in more detail elsewhere. [22] Both isomers of TBBT sublimed at 190-240 8C and both isomers of BDT sublimed at 55-80 8C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,14] The gas-phase photoelectron spectra of TBBT and BDT were collected by using the instrument and experimental procedures reported in more detail elsewhere. [22] Both isomers of TBBT sublimed at 190-240 8C and both isomers of BDT sublimed at 55-80 8C.…”
Section: Methodsmentioning
confidence: 99%
“…Anthony et al have recently demonstrated [6] that, as in the case of pentacene, directed functionalization of the central ring of ADT further increases the solubility and tunes the solid-state ordering in favor of p stacking. More recently, some of us [13,14] reported two thienobisbenzothiophene (TBBT) isomers (see Figure 1), in which, in comparison to ADT, the central benzene ring is also replaced with a thiophene ring. The X-ray analysis [14] of the anti-TBBT isomer reveals a favorable molecular overlap along the crystal c axis, which suggests that TBBT and their derivatives might be promising materials for applications in organic electronics.…”
Section: Introductionmentioning
confidence: 99%
“…32 There are also examples of the use of these heteroaryllithiums in addition reactions to aldehydes for the preparation of core-modified porphyrins, 33 hetero-calix [4]pyrroles, 34 benzo[b]thiophene analogues of pentacene 35 or inhibitors of type II 17β-hydroxysteroid dehydrogenase, 36 as well as in additions to phenanthrolines. 37 2-Alkylation reactions of the corresponding 2-thienyllithiums have been used, for instance, in the synthesis of dialkyloligothiophenes for molecular electronic applications.…”
Section: Methodsmentioning
confidence: 99%
“…30 Examples of the use of 2-lithiothiophenes for bromination reactions in the synthesis of oligothiophenes, 31 or for double addition to 2-thienylcarboxylated compounds in the preparation of multicharged methinium compounds can be found. 32 There are also examples of the use of these heteroaryllithiums in addition reactions to aldehydes for the preparation of core-modified porphyrins, 33 hetero-calix [4]pyrroles, 34 benzo[b]thiophene analogues of pentacene 35 or inhibitors of type II 17β-hydroxysteroid dehydrogenase, 36 as well as in additions to phenanthrolines. 37 2-Alkylation reactions of the corresponding 2-thienyllithiums have been used, for instance, in the synthesis of dialkyloligothiophenes for molecular electronic applications.…”
Section: Methodsmentioning
confidence: 99%